Best practices in surgical and nonsurgical management of head and neck Merkel cell carcinoma: An update. Issue 1 (11th November 2022) - Duarte‐Bateman, Daniela; Shen, Alan; Bullock, Taylor; Sadeghi, Payam; Escandón, Joseph M.; Dedkova, Eliska; Gastman, Brian R.
Abstract: Merkel cell carcinoma (MCC) is a rare, highly aggressive cutaneous neuroendocrine carcinoma. Controversy exists regarding optimal management of MCC as high‐quality randomized studies and clinical trials are limited, and physicians are bound to interpret highly heterogeneous, retrospective literature in their clinical practice. Furthermore, the rising incidence and notably poor prognosis of MCC urges the establishment of best practices for optimal management of the primary tumor and its metastases. Herein, we summarized the relevant evidence and provided an algorithm for decision‐making in MCC management based on the latest 2021 National Comprehensive Cancer Network guidelines. Additionally, we report current active MCC clinical trials in the United States. The initial management of MCC is dependent upon the pathology of the primary tumor and presence of metastatic disease. Patients with no clinical evidence of regional lymph node involvement generally require sentinel node biopsy (SLNB) while clinically node‐positive patients should undergo fine needle aspiration (FNA) or core biopsy and full imaging workup. If SLNB or FNA/core biopsy are positive, a multidisciplinary team should be assembled to discuss if additional node dissection or adjuvant therapy is necessary. Wide local excision is optimal for primary tumor management and SLNB remains the preferred staging and predictive tool in MCC. The management of MCC has progressively improved in the last decade, particularly due to the establishment of immunotherapy as a new treatment option in advanced MCC. Ongoing trials and prospective studies are needed to further establish the best practices for MCC management.